PEDAGOGICAL AND SOCIAL PERSPECTIVES ON THE APPLICATION OF ARTIFICIAL INTELLIGENCE IN THE EDUCATION SYSTEM - Kuttibekova, Guljan Tulepbaevna (SCIENCE and SOCIETY, 2026)
The article examines the pedagogical and social aspects of using artificial intelligence in the education system. It analyzes the potential of AI in creating individualized learning pathways for students, automating teachers’ work, and forming digital profiles.